On the Boundedness of Solutions of a Non-autonomous Differential Equation of Second Order - Tunç, Cemil (Sarajevo Journal of Mathematics, 2024)
We study the boundedness of the solutions to a non-autonomous differential equation of second order. With this work, we improve some stability results in the literature of boundedness of the solutions. We give two examples to illustrate the theoretical analysis in this work. 2000 Mathematics Subject Classification. 34C11, 34D20